Strengthening Tolerance Among High School Students Through Local History Education Based on Multicultural Values in West Kalimantan - Eka Jaya Putra Utama; Syahruddin Usman; Erwin Hafid; Arnadi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The purpose of this study is to analyze the tolerance attitudes of high school students in West Kalimantan. The study focuses on local history learning based on multicultural values. This study uses a qualitative approach to examine the phenomenon of learning in strengthening students' tolerance attitudes. Data were collected through interviews, direct observation, and document study. Data analysis used an interactive model and examined data validity through triangulation. The results of the study indicate that the implementation of local history learning through various methods, including the integration of interactive activities such as visits to historical sites, museums, and cultural exhibitions, is effective. The role of history teachers is crucial in creating an inclusive learning environment that values all cultural backgrounds. Through the integration of multicultural values-based local history education, students learn to appreciate individuals regardless of their group affiliations and cultural backgrounds. As a result, the values instilled will strengthen tolerance, fostering harmony amidst diversity.